2012
DOI: 10.5194/bg-9-3721-2012
|View full text |Cite
|
Sign up to set email alerts
|

Technical Note: Reactivity of C1 and C2 organohalogens formation – from plant litter to bacteria

Abstract: Abstract. C1/C2 organohalogens (organohalogens with one or two carbon atoms) can have significant environmental toxicity and ecological impact, such as carcinogenesis, ozone depletion and global warming. Natural halogenation processes have been identified for a wide range of natural organic matter, including soils, plant and animal debris, algae, and fungi. Yet, few have considered these organohalogens generated from the ubiquitous bacteria, one of the largest biomass pools on earth. Here, we report and confir… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 46 publications
0
18
0
Order By: Relevance
“…It suggests that there may be a potential concern for nitrogenous DBPs in managing drinking water supply following wildfires, especially during the first leaching events. In this study, the TS extracts did not show as high SHAN-FP as later extracts of SLS, suggesting that the reactive fire-produced HAN precursors in the AS were possibly photo-/bio-degraded/transformed, or rapidly diluted with less reactive precursors such as the recovered plant/ soil-derived carbon-rich DOM (Wang et al, 2012) under field conditions. Thus, although HANs are an important concern as they are more potent carcinogens than common carbonaceous DBPs such as THMs or HAAs (Richardson et al, 2007) and high SHAN-FP has been found in lab-burned ashes (>10 mg-HAN/mg-DOC; Majidzadeh et al, 2015;Wang et al, 2015b), the extremely high reactivity of DOM to form HANs observed for the sequential AS extracts may not persist in field AS samples (<5 mg-HAN/mg-DOC in Wang et al, 2015a) or source waters ( 2.7 mg-HAN/mg-DOC in Writer et al (2014)).…”
Section: Dbp Precursors In Water Extracts From Ash/soilmentioning
confidence: 56%
See 1 more Smart Citation
“…It suggests that there may be a potential concern for nitrogenous DBPs in managing drinking water supply following wildfires, especially during the first leaching events. In this study, the TS extracts did not show as high SHAN-FP as later extracts of SLS, suggesting that the reactive fire-produced HAN precursors in the AS were possibly photo-/bio-degraded/transformed, or rapidly diluted with less reactive precursors such as the recovered plant/ soil-derived carbon-rich DOM (Wang et al, 2012) under field conditions. Thus, although HANs are an important concern as they are more potent carcinogens than common carbonaceous DBPs such as THMs or HAAs (Richardson et al, 2007) and high SHAN-FP has been found in lab-burned ashes (>10 mg-HAN/mg-DOC; Majidzadeh et al, 2015;Wang et al, 2015b), the extremely high reactivity of DOM to form HANs observed for the sequential AS extracts may not persist in field AS samples (<5 mg-HAN/mg-DOC in Wang et al, 2015a) or source waters ( 2.7 mg-HAN/mg-DOC in Writer et al (2014)).…”
Section: Dbp Precursors In Water Extracts From Ash/soilmentioning
confidence: 56%
“…The highly toxic nitrogenous DBPs such as haloacetonitriles (HANs) and N-nitrosodimethylamine (NDMA) (Plewa and Wagner, 2009), although unregulated, are often detected in chlorinated and chloraminated drinking waters, respectively (Lee et al, 2007;Shah and Mitch, 2012). Previous studies have clearly shown that different DOM chemical compositions have a wide range of reactivity with oxidants to form DBPs (Dotson et al, 2009;Lee and Hur, 2014;Wang et al, 2012Wang et al, , 2014. Wildfires cause major transformations in DOM quantity and chemical composition depending on fire temperature and oxygen availability (Bladon et al, 2014;Santin et al, 2015;Wang et al, 2015a,b).…”
Section: Introductionmentioning
confidence: 99%
“…Despite findings that specific HAN FP increases with a decreasing C/N ratio of the original organic matter during the humification process, 45 the enhanced specific HAN and NDMA FP with increasing burn severity cannot be simply explained by DON, TDN, DOC/TDN, or DOC/DON patterns (P > 0.05; Table 1). The change of organic nitrogen structure with increasing burn severity is probably the major factor because specific HAN FP linearly increased with P II,n (r 2 = 0.52, P < 0.001; Figure 3D) and decreased with P I,n (protein-like compound; r 2 = 0.59, P < 0.001; Figure S4, Supporting Information).…”
Section: ■ Results and Discussionmentioning
confidence: 92%
“…45 Before burning, the detritus contained a substantial amount of biopolymers, such as lignin and protein. The lignin phenols and aromatic moieties of proteins are both known to be highly reactive THM and HAA precursors, 45,46 e.g., up to 328 μg-THM/mg-C for acetosyringone and 138 μg-THM/mg-C for tyrosine. The fire consumes many of these precursors and transforms them to condensed aromatics (such as PAHs).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Generally specific THM formation of these biomolecules usually low than 10 μg-THM/mg-C except few exceptions such as tryptophan and tyrosine which can be over 100 μg-THM/mg-C (34,35). Differences from other previous studies, we examined DBP formation directly disinfecting bacterial cells.…”
Section: Microbial Cells and Cellular Components As Dbps Precursormentioning
confidence: 96%